FORMULASI DAN KARAKTERISASI NANOSTRUCTURED LIPID CARRIER (NLC) MINYAK ATSIRI PALA (MYRISTICA FRAGRANS) SERTA UJI AKTIVITAS ANTIOKSIDAN MENGGUNAKAN DPPH - Nur Fadilah, Alinda
Aging and skin cancer are skin problems that arise due to skin exposure to free radicals. To counteract these free radicals, the human body has the body's defense system in the form of endogenous antioxidants. However, under certain conditions, endogenous antioxidants are unable to reduce the free radicals produced. Therefore, exogenous antioxidant supplementation is needed. There are many natural ingredients that can be used as a source of antioxidants, one of which is widely reported to be nutmeg essential oil (Myristica fragrans). However, nutmeg essential oil has a problem, that it is easily degraded due to exposure to the external environment. To overcome these problems, nanostructured lipid carriers (NLC) can be used as carriers for nutmeg oil. This study aims to determine the NLC-Nutmeg Essential Oil formula as a topical preparation and to increase the antioxidant activity of NLC-Nutmeg Essential Oil. The optimizations carried out in this study include liquid lipid screening, optimization of the ratio of solid lipids and liquid lipids, optimization of the type of sonicator, screening of the type of surfactant, and optimization of the sonicator amplitudo. Optimization provides the best NLC-Nutmeg Essential Oil formula at the composition of cetyl alcohol 1.8% (w/v), almond oil 3% (w/v), nutmeg essential oil 1.2% (w/v), Tween 80 3.2 % (w/v), Plantacare® 1200 0.8% (w/v), and aqua demineral. NLC-Nutmeg Oil with the best formula has the characteristics of a particle size of 124.40 ± 4.69 nm, a polydispersity index of 0.35 ± 0.05, a zeta potential of -38.96 ± 3.55 mV, and an entrapment efficiency of 95.29 ± 0.55%. The antioxidant activity of NLC-Nutmeg Oil increased as indicated by a 2.9-fold decrease in IC50 from nutmeg essential oil's IC50. Stability data showed that the particle size of NLC-Nutmeg Essential Oil increased on storage at 2-8 o C starting on the 7th day. However, the entrapment efficiency and antioxidant activity of NLC-Nutmeg Oil was stable up to 14 days, which proves the good protection of NLC against the stability of nutmeg oil.